Beyond simple messaging: a review of crisis communication research in hospitality and tourism - Liu-Lastres, Bingjie (International journal of contemporary hospitality management, 2022)
Purpose Crisis communication is an essential component of crisis management in hospitality and tourism. Yet few studies have offered a clear impression of the state of knowledge in this area. As one of the early conceptual attempts, this study aims to contribute to the existing knowledge by analyzing, comparing and synthesizing the literature in crisis communication and hospitality and tourism research. This study also proposes a transactional and dynamic crisis communication model that lays the conceptual foundation for future research. Design/methodology/approach This study was guided by a theory synthesis approach and analyzed the related literature. More specifically, this study conducted a rapid review of the general crisis communication research and a conventional, systematic review of crisis communication research in hospitality and tourism. Based on the review findings, this study further develops a transactive and dynamic crisis communication model in hospitality and tourism, which is fundamental for future studies in this area. Findings The findings of this study are presented through a literature review of general crisis communication research and crisis communication research in hospitality and tourism and the development of a transactive and dynamic crisis communication model in hospitality and tourism. Research limitations/implications This study reviews the literature and develops an integrated model for crisis communication in hospitality and tourism. The findings of this study lay the conceptual foundation for crisis communication in hospitality and tourism and reveal future research venues. Practical implications By offering a state-of-the-art review and developing an integrated conceptual model, the findings of this study can help bridge the gaps between academics and practices as well as serve as references for practitioners to identify and develop effective crisis responses. Originality/value This paper represents an early effort to review crisis communication research in hospitality and tourism and conceptualize the subject area through an integrated model. The findings of this study contribute to the further conceptual development of crisis communication in hospitality and tourism.